Pengaruh Perlakuan Pencelupan Dan Perendaman Terhadap Perkecambahan Benih Sengon (Paraserianthes falcataria L.) - Marthen Marthen; Elizabet Kaya; Herman Rehatta (Faculty of Agriculture, Pattimura University, 2013)
In developing productive forests, seeds play a crucial role. The seeds of forests tree have physical condition of hard seed coat, especially Leguminoceae family. Silvicultural techniques that can overcome seed coat dormancy are dyeing and submersion of seeds. The knowledge and experience in breaking seed dormancy of Sengon (Paracerianthes falcataria L.) is rare, therefore it is necessary to study how to overcome seed dormancy. The objective of this study was to determine the effect of dyeing and submersion treatments to overcome seed dormancy of Sengon seed to improve its viability. This research used Completely Randomized Design (CRD) with two factors: namely Seed (Factor A), dipped in hot water at 60 º C for (A0 = Control, A1 = 2 minutes, A2 = 4 minutes, A3 = 6 minutes), Factor B, seeds soaked in cold water: (B0 = control, B1 = 6 hours of soaking, B2 = 12 hours, B3 = 18 hours, B4 = 24 hours). The parameters observed were germination percentage, germination rate and vigor index. The results showed that among all parameters observed the interaction of factors A1B2, A2B2 and A3B2 were the best treatment for germination percentage which was equal to 100 percent, the best germination rate of 3.897 days and the best vigor index of 27.02